Cultura e ruína: o punk rock britânico da década de 1980 - Marques, Victor Otávio Carvalho (2015)
The present work aims to analyze the way that the British punk rock from the 1980‟s be part of our culture. Its intent is embrace a marginal cultural process through and from disposed phonographic elements. It is urgent this discussion by this cover possible composites to the observation of our mediatic, especially in music, on the end of the XX century, that the changes, mostly technical, progress faster. We contrast, as a hypothesis, that this subscription to the margins of culture is descendant of choices of each group analyzed here made instead of fame, figuring another relationship with the cultural development previewed by Iuri Lótman. Therefore, we embraced theoretical apparatus divided in two big parts: studies about the voice and its insertion in cultural series that it makes part and different cultural studies. We jut, here, the figures of Paul Zumthor, the aforementioned Iuri Lótman, Jesús Martín-Barbero, Walter Benjamin, Giorgio Agamben and Jerusa Pires Ferreira. The conclusion we point is a change of all the musical production scheme nowadays, this market having known radical changes and counter devices tacit for the undergrounds created by pun rock